2018
DOI: 10.1371/journal.pone.0197282
|View full text |Cite
|
Sign up to set email alerts
|

Use of the emergency department by refugees under the Interim Federal Health Program: A health records review

Abstract: IntroductionIn June 2012, the federal government made cuts to the Interim Federal Health (IFH) Program that reduced or eliminated health insurance for refugee claimants in Canada. The purpose of this study was to examine the effect of the cuts on emergency department (ED) use among patients claiming IFH benefits.MethodsWe conducted a health records review at two tertiary care EDs in Ottawa. We reviewed all ED visits where an IFH claim was made at triage, for 18 months before and 18 months after the changes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A health records review indicated that such Canadian Refugee Health Policy Reforms had decreased access to regular family doctors and created barriers to emergency care ( e.g. higher rate of rejected claims) for refugee patients (Bakewell et al , 2018). This financial cutback may further intensify clinicians’ bias and prejudice towards refugees as ‘demanding’ patients (Spitzer, 2004; McKeary and Newbold, 2010), due to refugees’ increasingly stringent insurance and burdensome paperwork (Edge and Newbold, 2013).…”
Section: Empirical Synthesismentioning
confidence: 99%
“…A health records review indicated that such Canadian Refugee Health Policy Reforms had decreased access to regular family doctors and created barriers to emergency care ( e.g. higher rate of rejected claims) for refugee patients (Bakewell et al , 2018). This financial cutback may further intensify clinicians’ bias and prejudice towards refugees as ‘demanding’ patients (Spitzer, 2004; McKeary and Newbold, 2010), due to refugees’ increasingly stringent insurance and burdensome paperwork (Edge and Newbold, 2013).…”
Section: Empirical Synthesismentioning
confidence: 99%
“…6 In fact, the admission rates for refugee children at Sick Kids Hospital in Toronto nearly doubled. 7,8 As a result of their ethical responsibilities to treat patients in emergencies, many public hospitals across the country absorbed the costs of providing care for uninsured refugee themselves. 10 The University Health Network in Toronto, for instance, reported an unpaid service debt totalling greater than Can$800 000 for uninsured emergency services alone due to the IFHP reforms.…”
Section: Refugee Health Care Funding In Canadamentioning
confidence: 99%